Advanced nanomaterials for solar cells and light emitting diodes - Gao, Feng (Biologist) (Micro & nano technologies., 2019)
Advanced Nanomaterials for Solar Cells and Light Emitting Diodes discusses the importance of nanomaterials as the active layers in solar cells and light emitting diodes (LEDs), along with the progress of nanomaterials as the electron and hole transporting layers. Specifically, the book reviews the use of nano-morphology of polymers, small molecules, and the organic-inorganic perovskites as the active layers in solar cells and LEDs. The design, fabrication and properties of metal-oxide-based nano-structures as electron and hole transporting layers are also reviewed. In addition, the development of plasmonic nanomaterials for solar cells and LEDs is discussed. Each topic in this book includes an overview of the materials system from principles to process. The advantages, disadvantages and related methodologies are highlighted. The book includes applications based on materials and emphasize how to improve the performance of solar cells and LEDs by the materials design, with a focus on nanomaterials.